Effects of Radiation on Materials: 17th International Symposium 1996
DOI: 10.1520/stp16481s
|View full text |Cite
|
Sign up to set email alerts
|

The Toughness of Irradiated Pressure Water Reactor (PWR) Vessel Shell Rings and the Effect of Segregation Zones

Abstract: To establish the integrity of pressure water reactor (PWR) vessels it is necessary to determine the toughness of A508C1.3 steel at the end of its life, that is after thermal ageing and irradiation embrittlement. In safety analyses the toughness can be deduced from a reference curve set forth in the code (ASME or RCC-M). The validity of the reference curve has been verified for several years for unirradiated French reactor vessels. Tests were performed on specimens taken from materials having heterogeneities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, the A-segregation observed appears to begin at a lower value than the lowest limit of the 17¡8 range suggested by Torabi Rad et al Closer inspection revealed this to be when Ra. 6.…”
Section: Ingotmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the A-segregation observed appears to begin at a lower value than the lowest limit of the 17¡8 range suggested by Torabi Rad et al Closer inspection revealed this to be when Ra. 6.…”
Section: Ingotmentioning
confidence: 99%
“…The enriched steel contained within A-segregate channels has often been found to deliver poor mechanical properties, [4][5][6][7] and the discovery of A-segregates can result in material rejection. Hence, it is useful for the manufacturers of large ingots to predict the location and severity of these defects.…”
Section: Introductionmentioning
confidence: 99%